Adaptations to change of direction ability after eight weeks of strength or plyometric training in elite youth football players - Lerche, M.; Borup, A.; Callaghan, S. J.; Buckthorpe, M. (Research Quarterly for Exercise and Sport, 2025)
This study aimed to investigate the effects of plyometric (PT) or strength (ST) training on change of direction (COD) performance at two differing angles among highly trained youth footballers. Seventy-one national-level youth football players (14.6 ± 1.8 years) were randomly allocated to either an 8-week, twice weekly, plyometric (PT) or strength training (ST) group. Pre- and post-intervention testing consisted of measures of COD performance at 45 and 180º, as well as maximal strength assessed via Trap Bar Deadlift 5RM (TBD5RM) and reactive strength index (RSI) from a 40 cm drop jump, respectively. Changes from pre- to post-testing were assessed via mixed ANOVAs (p <= .05) and effect sizes. Both training groups improved TBD5RM (PT = 7.8%, p < .001, ES = 0.32. ST = 6.9%, p < .001, ES = 0.28) and RSI (PT = 15.9%, p < .001, ES = 0.59. ST = 15.6%, p < .001, ES = 0.64) measures. Significant improvement in 45° COD performance was found for both training groups (PT = 4.0%, p < .001, ES = -0.68. ST = 3.6%, p < .001, ES = -0.61), whilst neither group improved at 180° (PT = 0.8%, p = .192, ES = -0.17. ST = 0.8%, p = .282, ES = -0.23). No significant differences in changes were found between training groups. Both PT and ST were effective at enhancing maximal and explosive strength as well as COD performance measured at shallow angles. Neither method enhanced the sharp angle COD performance.